Pengaruh Brand Image, Service Quality dan Price terhadap Customer Satifaction dan Customer Loyalty Kopi Janji Jiwa - Fanesya Yul Fani; Unik Dwi Lestari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
As time grows and the population increases. Making the company and beverage sector experience a significant increase, one of the popular types at this time is the coffee industry. One way to retain existing consumers and attract potential buyers by paying attention to reputation. The strategy used is brand image. A good brand image can differentiate consumer brands with their choice of competing brands. The purpose of this study was to determine the effect of brand image, service quality and price on customer satisfaction and customer loyalty, then to determine the most dominant variable in influencing consumer interest in soul promise coffee. The sample in this study amounted to 222 respondents using purposive sampling data collection techniques. The data is then processed using the Structural Equation Model (SEM) method with smartPLS software. Based on the test results, it is known that Brand Image has no effect on Customer Satisfacion and Price also has no effect on Customer Satisfaction, then Service Quality also has no effect on Customer Satisfaction. While Brand Image has a positive effect on Customer Loyalty and Price has a positive effect on Customer Loyalty, then Customer Satisfaction has a positive effect on Customer Loyalty.